Permission to feel : unlocking the power of emotions to help our kids, ourselves, and our society thrive - Brackett, Marc A (Celadon Books, 2019)
Marc Brackett is a professor in Yale University<U+2019>s Child Study Center and founding director of the Yale Center for Emotional Intelligence. In his 25 years as an emotion scientist, he has developed a remarkably effective plan to improve the lives of children and adults <U+2013> a blueprint for understanding our emotions and using them wisely so that they help, rather than hinder, our success and well-being. The core of his approach is a legacy from his childhood, from an astute uncle who gave him permission to feel. He was the first adult who managed to see Marc, listen to him, and recognize the suffering, bullying, and abuse he<U+2019>d endured. And that was the beginning of Marc<U+2019>s awareness that what he was going through was temporary. He wasn<U+2019>t alone, he wasn<U+2019>t stuck on a timeline, and he wasn<U+2019>t “wrong” to feel scared, isolated, and angry. Now, best of all, he could do something about it. In the decades since, Marc has led large research teams and raised tens of millions of dollars to investigate the roots of emotional well-being. His prescription for healthy children (and their parents, teachers, and schools) is a system called RULER, a high-impact and fast-effect approach to understanding and mastering emotions that has already transformed the thousands of schools that have adopted it. RULER has been proven to reduce stress and burnout, improve school climate, and enhance academic achievement. This book is the culmination of Marc<U+2019>s development of RULER and his way to share the strategies and skills with readers around the world. It is tested, and it works.